In the black fantastic - Eshun, Ekow; Martin, Kameelah L.; Commander, Michelle D. (Cambridge (Mass) : MIT press, 2022)
Cave, Nick ; Chrisom, Sedrick ; Gallagher, Ellen ; Locke, Hew ; Mutu, Wangechi ; Newsome, Rasheed ; Ofili, Chris ; Rezaire, Tabita ; Smith, Cauleen ; Victor, Lina Iris ; Walker, Kara.
A richly illustrated exploration of Black culture at its most wildly imaginative and artistically ambitious, In the Black Fantastic assembles art and imagery from across the African diaspora. Embracing the mythic and the speculative, it recycles and reconfigures elements of fable, folklore, science fiction, spiritual traditions, ceremonial pageantry, and the legacies of Afrofuturism. In works that span photography, painting, sculpture, cinema, graphic arts, music and architecture, In the Black Fantastic shows how speculative fictions in Black art and culture are boldly reimagining perspectives on race, gender and identity. Standing apart from Western narratives of progress and modernity premised on the historical subjugation of people of color, In the Black Fantastic celebrates the ways that Black artists draw inspiration from African-originated myths, beliefs, and knowledge systems, confounding the Western dichotomy between the real and unreal, the scientific and the supernatural. Featuring more than 300 color illustrations, this beautifully designed book brings together works by leading artists such as Kara Walker, Chris Ofili, and Ellen Gallagher; explores groundbreaking films like Daughters of the Dust and Get Out; considers the radical politics of pan-Africanism and postcolonialism; and much more.
In the black fantastic, Haward Gallery, London, 29 June - 18 September 2022
boek